Pemidanaan Terhadap Anak Di Bawah Umur dalam Penyalahgunaan Narkotika: Studi Kasus Putusan Pn Solok No.2/Pid.Sus -Anak/2018/Pn.Slk - Nurlisa Bani; Alfitra; Mara Sutan Rambe (UIN Syarif Hidayatullah Jakarta, 2025)
This study analyzes the criminalization of minors in narcotics abuse cases, as reflected in the Solok District Court Decision No. 2/Pid.Sus-Anak/2018/PN.Slk. Specifically, it explores the factors contributing to drug abuse among minors and the judicial considerations applied by the panel of judges in determining sanctions for juvenile offenders. The research employs a qualitative method with a statute approach, grounded in the Court Decision, Law No. 35 of 2009 on Narcotics, Law No. 35 of 2014 on Child Protection, and Law No. 11 of 2012 on the Juvenile Criminal Justice System. The findings reveal that drug abuse among minors is largely influenced by improper social interactions, which are further categorized into several triggering factors: family environment, social influence, education, psychological development, religious values, and geographical conditions. The court’s judgment in imposing sanctions on the child offender is examined from three perspectives, juridical, sociological, and philosophical while also considering the possible application of restorative justice through the diversion system. This study highlights the importance of balancing legal accountability with child protection principles in addressing juvenile narcotics offenses.